Enhancing Learners’ Geometric Thinking Using Dynamic Geometry Computer Software - Adelabu, Folake Modupe; Makgato, Moses; Ramaligela, Manto Sylvia (Journal of Technical Education and Training, 2019)
The appropriate use of dynamic geometry computer software in teaching and learning geometrical concepts is an essential factor of quality mathematics in secondary schools and TVET colleges. The aim of this study is to measure learners’ Geometric Thinking (GT) according to van Hiele model. The study was conducted with pre and posttest non-equivalent control group quasi-experimental method. The control group were taught by conventional method while the experimental group learnt geometry through the use of Dynamic Geometry Computer Software. Convenient and purposive sampling were used for participants’ selection. The sample of the study was 87 ninth grade learners. A GMAT on geometric thinking was used as the data collecting instrument. Data analysis was done according to Van Hiele theory using ANOVA. The result showed that there was significant difference in the GT levels of the experimental and control groups, but the GT points were the same. The indication means the use of DGCS increase the learners’ GT. The improvement will enable learners in both secondary and technical colleges to make informed decision and solve problem in various fields in the future. Since learners enroll to TVET colleges at grade nine, the improvement will also help the learners when encountering problem in geometry in vocation education training. Lack of sufficient geometry thinking in learning geometry, make learners to be deficient in building foundational geometry thinking skills and problem solving which are useful in TVET colleges. This study suggest that further study is necessary to extend the investigation to more topics across the mathematics curriculum both in secondary and TVET colleges.